PERANCANGAN SISTEM PRA PEMBERKASAN PENSIUN PNS BERBASIS WEB DI BKPSDM KABUPATEN GORONTALO - Hendra Agus; Hilmansyah Gani; Wahyudin Hasyim; Frangky Tupamahu (Akademika : Jurnal Ilmiah Media Publikasi Ilmu Pengetahuan dan Teknologi, 2026)
The pre-filing process for Civil Servant (PNS) retirement applications at the Regional Human Resources Development Agency (BKPSDM) in Gorontalo Regency is still carried out manually using physical documents, resulting in various obstacles, such as the risk of file loss, verification delays, and inefficient document submission and correction processes. This study aims to design a web-based Civil Servant Pre-filing System at the BKPSDM in Gorontalo Regency to improve the effectiveness and efficiency of pension administration services. The system development method used is the Waterfall method, which includes the stages of needs analysis, design, implementation, testing, and maintenance. The system was designed using UML modeling and built using the Laravel Framework. The results show that the designed system facilitates prospective retirees in submitting and correcting files online, assists verifiers in structured document verification, reduces the use of physical documents, and improves the effectiveness of pension administration management at the BKPSDM in Gorontalo Regency. Testing used the Black Box Testing method to demonstrate that all system functions operate according to established requirements